Corticosteroids in the treatment of IgA nephropathy: what do we learn from the TESTING trial - Ming-jing Pi; Jing Yuan; Lu Liu; Ping-hong He; Shan-shan Hu; Yan Zha (Linchuang shenzangbing zazhi, 2024)
IgA nephropathy (IgAN), the most common form of primary glomerulonephritis, is predominant in young adults and children. Corticosteroid therapy has been controversial over several past decades. TESTING (Therapeutic Effects of Steroids in IgA Nephropathy Global) study, initiated in 2012, is an international, multicenter, double-blinded, randomized and placebo-controlled trial for evaluating oral methylprednisolone’s safety and long-term efficacy under conditions of optimized supportive treatment in IgAN patients at an elevated risk of progression. After one decade of efforts, successful completion of TESTING indicated that a 6 to 9 month course of oral methylprednisolone has been an effective regimen of protecting kidney function in high-risk IgAN patients. Some safety concerns persisted. Compared with a full-dose regimen, reduced-dose regimen was beneficial with higher safety. Overall, the TESTING trial provided more robust data regarding the treatment dosage and safety of corticosteroids. It has important implications for IgAN children. With a deeper pathogenetic understanding of IgAN, ongoing studies of novel therapeutic regimens shall further optimize the benefit-risk ratio.